2005
DOI: 10.1016/j.adnc.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Stress in Chinese-American Parents of Infants Cared for in the Intensive Care Unit

Abstract: Findings from this study suggest implications for the education of both families and the ICU staffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 32 publications
3
42
2
Order By: Relevance
“…While sleep deprivation could be a symptom of parental stress (S. Y. Lee et al, 2005; S. Y. Lee & Kimble, 2009), it could also become a stressor for mothers in its own right, causing these women's allostatic loads to exceed their thresholds and leading to adverse mental health effects (Ganzel, Morris, & Wethington, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While sleep deprivation could be a symptom of parental stress (S. Y. Lee et al, 2005; S. Y. Lee & Kimble, 2009), it could also become a stressor for mothers in its own right, causing these women's allostatic loads to exceed their thresholds and leading to adverse mental health effects (Ganzel, Morris, & Wethington, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies with mothers with infants in the NICU have correlated poor sleep with fatigue and depressive symptoms (Lee & Kimble, 2009; S. Y. Lee, K. A. Lee, Rankin, Alkon, & Weiss, 2005;Stremler, Dhukai, Wong, & Parshuram, 2011). The determination of mitigating factors for sleep, such as light exposure, may allow for the development of preventive strategies.…”
mentioning
confidence: 99%
“…A life change may be the birth of a preterm infant or transition to the role of motherhood, whereas chronic stress may relate to demographic variables, such as financial burden, relationship strain, or social discrimination. Researchers have shown that mothers with a newborn in the NICU describe this as an extremely stressful experience [15][16][17][18] , and there is a positive linear association between high stress perception and severe depressive symptoms and poor sleep quality in mothers with preterm infants [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Limited literature exists for mothers with a preterm infant, and less is known about their rates of postpartum depression, stress, sleep disturbances, and well-being while their infant remains in the NICU. Compared to the general population, mothers with an infant in the NICU may be more vulnerable to depressive symptoms due to stress they endure in association with their preterm infant's medical conditions [16] . This study aimed to compare perceived stress, sleep characteristics, and well-being (fatigue, health-related quality of life) in NICU mothers categorized as having high or low depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the stress literature were incongruent about whether different infant and parental characteristics were associated with stress levels in the NICU parents (Ichijima, Kirk, & Hornblow, 2011;Mackley, Locke, & Spear, 2010;Reid & Bramwell, 2003;Turan et al, 2008). A small number of investigators evaluated predictors of stress in NICU parents (Dudek-Shriber, 2004;Lee, Lee, Rankin, Alkon, & Weiss, 2005;Meyer et al, 1995;Shields-Poë & Pinelli, 1997). Numerous researchers investigated the topic of parental stress but few investigators explored parental uncertainty and predictors of uncertainty experienced by parents with infants in the NICU (Lam, Spence, & Halliday, 2007;.…”
Section: Background and Significancementioning
confidence: 99%